Peran Kepala Sekolah Dalam Manajemen Sarana Dan Prasarana Pendidikan di SDN Cibuntu 04 - Almaida, Dimas Kurnia; Fahmi, Ilham (Jurnal Ilmiah Wahana Pendidikan, 2023)
Educational infrastructure and facilities are factors that contribute to the success of the learning dan teaching process in schools. In addition, the role of the principal in controlling and administering these facilities has a substancial impact on the efficacy and efficiency of learning in the school. This research used the observation method to acquire data via interviews and classroom observations. This research intends to examine the principal's involvement in the management of facilities and infrastructure. According to the results, the principal has the following primary responsibilities: 1) Provide; 2) Procurement; 3) Advise; 4) Regulate the maintenance, and 5) Oversee the management of facilities and infrastructure.